Energy dissipation in multifrequency atomic force microscopy - Pukhova, Valentina; Banfi, Francesco; Ferrini, Gabriele (Beilstein Journal of Nanotechnology, 2014)
The instantaneous displacement, velocity and acceleration of a cantilever tip impacting onto a graphite surface are reconstructed. The total dissipated energy and the dissipated energy per cycle of each excited flexural mode during the tip interaction is retrieved. The tip dynamics evolution is studied by wavelet analysis techniques that have general relevance for multi-mode atomic force microscopy, in a regime where few cantilever oscillation cycles characterize the tip–sample interaction.
Keywords: band excitation; multifrequency atomic force microscopy (AFM); phase reference; wavelet transforms